A thermo-sensitive, injectable and biodegradable in situ hydrogel as a potential formulation for uveitis treatment. Issue 28 (20th June 2019) - Zou, Mengwei; Jin, Rongrong; Hu, Yanfei; Zhang, Ying; Wang, Haibo; Liu, Gongyan; Nie, Yu; Wang, Yunbing
Abstract : The thermo-sensitive hydrogels with high drug loading rate achieved sustained drug release over 2 weeks. Histopathological examination of retina confirmed the excellent biocompatibility and effective anti-inflammatory property of the hydrogel. Abstract : Indomethacin (IND) is a nonsteroidal anti-inflammatory drug (NSAID), which is widely used to relieve inflammation. However, general eye drops cannot reach lesions efficiently due to the presence of complicated and special biological barriers in the eye. Repeated administration of this drug for chronic ophthalmic diseases also showed poor patient compliance. Herein, an in situ injectable thermo-sensitive hydrogel of indomethacin-conjugated polymer was fabricated to overcome these crucial problems. The poly(NIPAAm- co -MAA- co -HTI) (PNMHTI) hydrogel, composed of N -isopropylacrylamide (NIPAAm), methacrylic acid (MAA), and 2-hydroxylethyl methacrylate- g -poly(trimethylene carbonate)-indomethacin (HEMA- g -PTMC-IND) (HTI), was synthesized by radical polymerization of NIPAAm, MAA and HTI. According to the rheology investigation, the sol–gel conversion temperature of the hydrogels was around 33 °C, and the sol–gel transition occurred at physiological temperature (37 °C). The release of indomethacin from the injectable hydrogels was sustained for over 2 weeks in phosphate buffer saline with esterase due to the sustained biodegradable behavior by the hydrolytic cleavage of the residual PTMC chains. In addition, these hydrogels displayed excellent biocompatibility against mouse fibroblasts, reduced cytotoxicity for indomethacin and a significant anti-inflammatory effect against macrophages. Uveitis was successfully established in New Zealand rabbits, and the PNMHTI hydrogels were injected into the vitreous body. Histopathological examination of retinas confirmed the good biocompatablity and anti-inflammatory effects of PNMHTI hydrogels in vivo . Overall, the PNMHTI hydrogels reported herein offer an attractive biomaterial-centered treatment option for uveitis.